An institutional metaphysics for the Trinity - Michaël Bauwens (TheoLogica, 2022)
This paper explores and defends an institutional metaphysics for the Trinity as providing us with an inherently interpersonal reality, and provides general and specific methodological arguments in that direction in the first section. The actual argumentation is then first of all directed against Augustine’s rejection of the family as a suitable analogy for the Trinity. It is instead argued that the family does in fact offer an interesting and suitable analogy. Next, several more general and historic precursors to such an institutional analogy are explored and fleshed out, relying on the legal and economic meaning of the term ‘substance’ as an estate, such as the shared inheritance between a father and a son. The main section further develops the outlines and main features of such an institutional metaphysics, relying on both analogies to result in three persons in one numerically identical substance. The final section returns to the methodological issue but now in an explicitly Marian key, culminating in the Holy Family as a key exemplar for the family analogy.